INOVASI PEMBELAJARAN BERBASIS TEKNOLOGI SEBAGAI STRATEGI PENJAMINAN MUTU DI SMP NEGERI 2 ARJASARI KABUPATEN BANDUNG: A technology-based learning innovation model for quality assurance in rural junior high schools - Hidayat, Atep Rustandi; Ramdani, Wahyu; Ferdyansyah, Ferry; Nevelin, Susi Lutfiah (Perkumpulan Peneliti dan Pegiat Literasi, 2025)
This study examines technology-based learning innovation as a quality assurance strategy at SMP Negeri 2 Arjasari, a junior high school in a rural area of Bandung Regency, Indonesia. Despite limited technological infrastructure, the school has implemented creative solutions to improve learning quality through teacher-driven innovations. Using a qualitative case study approach, data were collected through classroom observations, in-depth interviews with the principal and teachers, and document analysis from January to April 2025. The findings show that strategic resource management, including shared use of projectors and adaptation of personal devices, combined with project-based learning methods, significantly enhanced student engagement and learning outcomes. The study confirms that effective technology integration in resource-limited environments relies more on pedagogical innovation and teacher collaboration than on infrastructure availability. These results challenge conventional assumptions about the relationship between technology and educational quality, offering an alternative model relevant to rural schools in developing countries. This research enriches the discourse on educational technology by highlighting context-appropriate innovation strategies and their implications for quality assurance frameworks in low-resource settings. The findings extend the concept of process-based quality assurance in schools with limited resources.